Letter - Trabal, Francesc, 1899-1957
032-0190-001 Mr Bolton Barcelona, November, 22nd. 1938. DEPARTAMENT D'ECONOMIA SERVEI DE RESTAURANTS INFANTILS Sir WALTER CITRINS, General Secretary of the National Council of Labour, LONDON. Dear Sir: The festivities of Christmas and New Year Day are approching. These festivities are full in all the world of familiar emotion and characterized everywhere by the reunion of the families and by the homage to the children. We, who are living all the hardness and all the sorrows of the war, we should wish to be able to do something for to bring to our children somewhat of the rejoicing of these traditional festivities. We can't bring them the joy of a reunite family, because the fathers and brothers are in the battle front, but we could give them toys and dainties which they don't know a long time ago. It is for this motive, that this "Seccio de Relacions i Propaganda" del Servei de Restaurants Infantils del Departament d'Economia de la Generalitat de Catalunya" (Section of Relations and Propaganda of the Infantile Restaurant Service of the Economy Department of the Generality of Catalonia) applies to you. Our service, which nourishes every day in Barcelona to 40 thousand children and has also several Restaurants distributed in the rest of Catalonia, would like to increase its possibilities, would give to the children it has shelted a sensation of splendor. Receive this petition we do, with all your interest: think to our babies, subjected to the inclemencies of the war and to all the difficulties emanated of it, and let them know the fervour of your sympathy and of your affection. Send us what you freely can: foods, clothes, toys, money. You can send your gifts directly or by the Committee of Aid to Spain" or put you in relation with the nearest consulate which will give you all the data you need to realize the expedition. You must note always that the gifts are destined to the "Servei de Restaurants Infantile - Department d'Economia de la Generalitat de Catalunya". Receive this petition with interest and propagate it: inform of itself to your friends, to the societies you belong; communicate to everybody that the children of Catalonia wait to next festivities of Christmas and New Year Day a proof of remembrance, of affection and of tenderness which come to then from far away of our mountains and of our seas, and speak them of other children more fortunate who in their happiness do not forget our suffering babies. Sincerely grateful for all you may do for us, we greet you with all our affection. "Seccio de Relacions i Propaganda" Francesc Trabal 292/946/32/190